Autonomous mobile robot (AMR) integrated chassis control considering active-fault tolerant control - Muhammad Bin Shamsudin (Nanyang Technological University, 2023)
This report presents a comprehensive study of control strategies for Autonomous Mobile Robots (AMRs). Specifically, the report focuses on the implementation of two control strategies, Model Predictive Control (MPC) and Proportional Integral Derivative (PID), for collision avoidance in the AMR system. Additionally, the report discusses the implementation of four Active Fault Tolerant Control (AFTC) algorithms for the AMR's actuators. The results of simulations demonstrate that both MPC and PID controllers are effective in controlling the AMR system and avoiding collisions. Moreover, all four AFTC algorithms were effective in ensuring the AMR can move linearly in the horizontal direction when there is a fault in the driving actuator(s). The study highlights the importance of effective control strategies for AMR systems and can be useful for further research on AMR systems and their applications in various industries.